Enhanced electrochemical oxidation process with hydrogen peroxide pretreatment for removal of high strength ammonia from semiconductor wastewater. (October 2020) - Chung, Seungjoon; Chung, Jinwook; Chung, Chongmin
Abstract: Electrochemical oxidation (EO) process was investigated for decomposing ammonia in wastewater from semiconductor industry. This wastewater typically contains high concentration of hydrogen peroxide as well as ammonia in nature. As results of lab test, the presence of hydrogen peroxide exhibited a significant negative effect on ammonia removal efficiency, which was described by an oxidant-scavenging reaction pathway with recurrence relationship. Hydrogen peroxide removal by activated carbon was proposed as a pretreatment of EO process not only for the enhancement of reaction rate but also for the stability of effluent quality. As results of pilot test, ammonia removal rates were enhanced 2 ∼ 3.5 times after pretreatment. In addition, economic analysis results indicated that operating expense with pretreatment was about 60 % of that without pretreatment, which was about 30 % less than that in conventional chlorination without addition of hazardous chemicals. The suggested process has great potential for alternative to conventional chlorination in treatment of high strength ammonia wastewater from semiconductor industry.